Study of outcomes of transobturator tape fixation in management of stress urinary incontinence - Chaudhari, Manali Anil; Darawade, Sameer P.; Amol Sasane, Aparna; Medankar, Nikita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Stress urinary incontinence (SUI) is one of the most chronic conditions significantly impacting the quality of daily life of 15-40% of female population because of the involuntary escape of urine on exertion due to sudden rise in intraabdominal pressure. Transobturator tape (TOT) fixation is the leading surgical intervention in managing SUI if the conservative management fails because of its lesser postoperative complications, shorter hospital stay, lesser recurrence rate and easy to perform compared to other surgical interventions available hence enhancing the quality of life with women with SUI. TOT fixation therefore has the full potential to be the gold standard in the management of SUI. Methods: It is a prospective observational study conducted in the Gyanecology ward of SKNMCGH, Pune for 3 years with apparatus and material available in the institute on 32 patients based on the inclusion criteria; all females with stress urinary incontinence willing for surgical management. Women not willing for surgical intervention, also women with mixed urinary incontinence and patients who had previous corrective surgery for stress urinary incontinence were excluded. The TOT procedure was performed by outside in technique. Results: Success rate of TOT fixation was 96.9%. A total of 31 patients (96.9%) were cured whereas 1 (3.1%) experienced surgical failure. Conclusions: Transobturator tape fixation is an effective method of management for SUI as it is associated with low morbidity, lesser postoperative complications and therefore has full potential to be the new gold standard for treating SUI.